2019
DOI: 10.3390/atmos10120741
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Daily Rainfall Regime in Southern West Africa

Abstract: Extreme climate events, either being linked to dry spells or extreme precipitation, are of major concern in Africa, a region in which the economy and population are highly vulnerable to climate hazards. However, recent trends in climate events are not often documented in this poorly surveyed continent. This study makes use of a large set of daily rain gauge data covering Southern West Africa (extending from 10° W to 10° E and from 4° N to 12° N) from 1950 to 2014. The evolution of the number and the intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 40 publications
10
24
0
Order By: Relevance
“…6a) is characterized by drying in southern Ivory Coast and southern Ghana, moderate moistening in central Ivory Coast and central Ghana, and strongly positive trends in the north-east. Averaged over our study region, the trend is positive, which is consistent with recent studies by Bichet and Diedhiou (2018) and Nkrumah et al (2019). As for the LDS, the overall agreement between stations and CHIRPS is good, but coastal stations tend to show more positive trends than the immediate CHIRPS neighbours.…”
Section: Second Rainy Seasonsupporting
confidence: 91%
“…6a) is characterized by drying in southern Ivory Coast and southern Ghana, moderate moistening in central Ivory Coast and central Ghana, and strongly positive trends in the north-east. Averaged over our study region, the trend is positive, which is consistent with recent studies by Bichet and Diedhiou (2018) and Nkrumah et al (2019). As for the LDS, the overall agreement between stations and CHIRPS is good, but coastal stations tend to show more positive trends than the immediate CHIRPS neighbours.…”
Section: Second Rainy Seasonsupporting
confidence: 91%
“…They pointed out that after the severe drought in the Sahel in the late 1960s, the last decade of the 20th century saw a partial recovery of rainfall, particularly in the central part of the Sahel, but without returning to the wet conditions of the 1950s and 1960s. In addition, recent studies have shown that the relative increase in rainfall accumulation was mainly linked to an increase in the intensity of rainfall events, while the occurrence of rainfall events remains at an average level close to that of periods of extreme drought [25,26]. Therefore, the terms "recovery" or "return to wet conditions" often used to characterize rainfall over the past two decades has to be considered with caution.…”
Section: Introductionmentioning
confidence: 99%
“…Lebel and Ali [16] then Panthou et al [25] have shown that there are contrasts between the Western Sahel which seems to start a later recovery in annual precipitation than the central Sahel. Nkrumah et al [26] showed that contrast also exists between sub-regions with in the Southern West Africa with a more marked increase in coastal than inland regions. It is also what Diop et al [28] have shown in a recent study in Senegal where rainfall recovery in recent decades is significant in the coastal strip of Senegal.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, the atmospheric patterns specifically associated with intense rainfall events in West Africa in general, and Guinean West Africa in particular, are poorly known. The spatial patterns of extreme rainfall distribution were analysed [20] as well as their recent trends [21,22], but these studies did not consider the atmospheric circulation. Sossa et al [23] found that intense daily rainfall events in West Africa were modulated by the MJO in March-May and June-September.…”
Section: Introductionmentioning
confidence: 99%